Aging, trends in CD4+/CD8+ cell ratio, and clinical outcomes with persistent HIV suppression in a dynamic cohort of ambulatory HIV patients. (1st May 2022) - Novak, Richard M.; Armon, Carl; Battalora, Linda; Buchacz, Kate; Li, Jun; Ward, Douglas; Carlson, Kimberly; Palella, Frank J.
Abstract : Background: Age blunts CD4 + lymphocyte cell count/μl (CD4 + ) improvements observed with antiretroviral therapy (ART)-induced viral suppression among people with HIV (PWH). Prolonged viral suppression reduces immune dysregulation, reflected by rising CD4 + /CD8 + ratios (CD4 + /CD8 + ). We studied CD4 + /CD8 + over time to determine whether it predicts risk for select comorbidities and mortality among aging PWH with viral suppression. Methods: We studied HIV Outpatient Study (HOPS) participants prescribed ART during 2000–2018 who achieved a viral load less than 200 copies/ml on or after 1 January 2000, and remained virally suppressed at least 1 year thereafter. We modeled associations of CD4 + /CD8 + with select incident comorbidities and all-cause mortality using Cox regression and controlling for demographic and clinical factors. Results: Of 2480 eligible participants, 1145 (46%) were aged less than 40 years, 835 (34%) 40–49 years, and 500 (20%) ≥ 50 years. At baseline, median CD4 + /CD8 + was 0.53 (interquartile range: 0.30–0.84) and similar among all age groups (P = 0.18). CD4 + /CD8 + values and percentage of participants with CD4 + /CD8 + at least 0.70 increased within each age group ( P  < 0.001 for all). CD4 + /CD8 + increase was greatest for PWH aged less than 40 years at baseline. In adjusted models, most recent CD4 + /CD8 + less than 1.00 and less than 0.70 were independently associated with higher risk of non-AIDS cancer and mortality, respectively. Conclusion: Pretreatment immune dysregulation may persist as indicated by CD4 + /CD8 + less than 0.70. Persistent viral suppression can improve immune dysregulation over time, reducing comorbidity, and mortality risk. Monitoring CD4 + /CD8 + among ART-treated PWH with lower values provide a means to assess for mortality and comorbidity risk.